Análisis de impacto, percepción del riesgo y adopción de estrategias de mitigación entre agricultores del estado de Níger, Nigeria, África - Olufemi Adekunle, Adedayo; Olanrewaju Babatunde, Rapheal; Durojaiye Ayeni, Matthew (Universidad Nacional Agraria, 2023)
In this study we used a recent cross-sectional survey data in Niger state, Nigeria to examine the relationship between shock impact, risk perception and adoption of risk mitigation methods among farming households in Niger state, Nigeria. The specific objectives are to; (i) describe risks perception among the farming households; (ii) examine the determinants of future risk perception among the farmers; and (iii) describe the mitigation methods applied by the house holds. A frequency table was used to describe impact and future risk perception; Ordinary Least Square (OLS) regression was used to analyze the determinants of future risk perception among the farming households, and a graph was used to describe the mitigation methods applied by the households. The result showed that the majority of the respondents experienced extreme weather events with the mean of 2 times per household and experienced the highest severity. The most perceived future risks in five year swere extreme weather events with a mean of 6 times per house holdover five years and predicted with the highest severity. OLS regression result showed that weather impact, biological impact,economic impact, socio-political impact and household head age were significant and positive determinants of future risk perception. While marital status was negatively related to future risk perception. The mitigation methods mostly employed in the area were drought-tolerant crops (63%), diversification of crop, plot and livestock(61%), buffer stock (55%), dry season irrigated rice farming (41%). The study recommends that farmers should be encouraged to diversify their sources of livelihood to boost their adaptive capacity. The government needs to invest more in the expansion of irrigation facilities to ensure all-year-round food production and to improve house holds’welfare.